Inclusion and inclusive education through the eyes of the majority in Slovakia - Šuhajdová, Ivana (Sodobna pedagogika, 2019)
This paper deals with inclusive education, primarily in relation to the awareness and opinions of the majority in Slovakia about this form of education. It points to the human factor as the key condition for the successful implementation of inclusive education. The paper presents the results of a research study that gathered the opinions of the majority in Slovakia on the implementation of inclusive education. The data was collected via a questionnaire with 557 respondents. Besides the quantitative statistics, the results were analysed by grounded theory methods. The collected data provides information on the persistent lack of awareness and orientation of the majority regarding the basic terminology of inclusive education. Additionally, we found a prevalent positive perception and attitude towards the implementation of inclusive education in regular Slovak schools by the majority, whereas the greatest issues related to its implementation were identified as the parents' concerns about the behaviour of the intact children already in the mainstream system towards children with disabilities and the inability of children with disabilities to become members of a group, concerns about specific types of disability, concerns about the quality and course of education, concerns about children with disabilities being bullied and concerns about the occurrence of unpredictable events.
Keywords: človeški dejavnik; disability; human factor; impairment; inclusion; inclusive education; inkluzija; inkluzivno izobraževanje; javnost; majority; oviranost; prikrajšanost; Slovak Republic; Slovaška